Molecular tools for differentiation of non-typeable Haemophilus influenzae from Haemophilus haemolyticus - Pickering, Janessa; Richmond, Peter C.; Kirkham, Lea-Ann S. (Frontiers in Microbiology, 2014)
Nontypeable Haemophilus influenzae (NTHi) and Haemophilus haemolyticus are closely related bacteria that reside in the upper respiratory tract. NTHi is associated with respiratory tract infections that frequently result in antibiotic prescription whilst H. haemolyticus is rarely associated with disease. NTHi and H. haemolyticus can be indistinguishable by traditional culture methods and molecular differentiation has proven difficult. This current review chronologically summarizes the molecular approaches that have been recently developed for differentiation of NTHi from H. haemolyticus, highlighting the advantages and disadvantages of each target and/or technique. We also provide suggestions for the development of new tools that would be suitable for clinical and research laboratories.